Retrotransposon-based molecular markers as a tool in delimiting species in section Ryncholotus, a recent radiation group of Macaronesian Lotus. Issue 2 (23rd October 2020) - Pérez-Vargas, Israel; Portero Álvarez, Ana M.; Pérez de Paz, Pedro L.; PÉrez, JosÉ A.
Abstract : Island species are particularly vulnerable to extinction and decline due to a range of factors, including isolation, small population sizes, climate change, or the introduction of alien species. Given their high levels of biodiversity, the preservation and protection of island endemic species are fundamental to reducing the loss of global diversity. Therefore, species delimitation, description and identification are among the most important tasks in conservation biology. However, determining species boundaries in some cases can be challenging, especially in groups that have radiated recently, where frequently used molecular markers do not have enough discrimination power. Thus, it is important to look for new approaches with higher resolution. In the present study, we test the use of retrotransposon-based molecular markers to investigate the taxonomic status of five endemic and endangered Lotus species in the Canary Islands. Our analysis revealed that the five species conform different entities, in concordance with their morphological differences, and shown that the technique named inter-Primer Binding Site (iPBS) is a reliable molecular marker system that allows to discriminate among Lotus and has a potential value for taxonomy and conservation.